Guidance and Counseling Study Program Students’ Perception towards Bahasa Inggris Course - Yasminar Amaerita Telaumbanua (JELITA, 2024)
The research objective was to find out, to analyze and to describe guidance and counseling study program students’ perception towards Bahasa Inggris course learnt. Type of the research was quantitative descriptive analysis. The number of research participants was 45 students. The method used in collecting and analyzing data was by using quantitative approach and descriptive analysis which was presented by a variety of means and Likert Scale, collected through instrument that was questionnaire distributed to students with 25 statements. As research finding, students’ perception towards Bahasa Inggris course was ‘disagree’ with the obtained grand mean was 1.907 scored range 1.81-2.60 of Likert Scale. The finding was supported by the frequency of highest dominant scale was neutral which was more than a half of 25 statements and the choice of statements described students’ readiness was unprepared that were caused by two factors, either internally and externally. In conclusions, students’ perception indicates negative since most of students chose ‘neutral and disagree’ scales if it was compared to ‘strongly agree and agree’ scales towards the statements about Bahasa Inggris course.